A STUDY ON THE EFFECT OF THE BEARING CLEARANCE OF THE WHEELS ON THE MOVEMENT OF THE BAND SAW BLADE - Atanasov, Valentin; Nikolov, Petar (Innovation in Woodworking Industry and Engineering design, 2021)
The present work refers to verification of the axial run-out of the band saws blades in band saw machines, as their geometric accuracy. It has been determined that the axial force is applied when rotating the wheels by hand, which, in the presence of bearing clearances, results in a displacement of the band saw blade in one direction for each complete rotation which does not allow its geometric accuracy to be determined. The effect of the bearing clearances of the wheels on the trajectory described by the back part of the band saw blade is studied. The deflection of the crown of the guide wheels when applying a force of 150 N in the direction of feed for worn and new bearings was measured, as well as the displacement of the back of the band saw blade in this direction for these two bearings. Displacement of 0.2 – 1.1 mm of the band saw blades in one direction has been detected for each complete rotation which depends on the condition of the bearings. It is recommended that such verification should be carried out on relatively new bearings and that no axial force will be applied to worn ones.